Queen Alexandra was not the widow of Judah Aristobulus I - Scales, Joseph (Journal for the study of the pseudepigrapha, 2024)
This article assesses the state of the question on the identity of Alexandra, Queen of Judea, in the period before her regency. Currently, outside of a few select publications, the field identifies Alexandra with the widow of Judah Aristobulus I. The following argument demonstrates that Queen Alexandra cannot have been married to Aristobulus, having had a child with her husband Alexander Jannaeus before the death of Aristobulus. This argument has been previously presented in scholarship but has not received much attention, likely due to the focus of previous arguments being on the plausibility of a Levirate marriage between Alexandra and Jannaeus. This article seeks to redress this imbalance and clearly state the case against an ongoing misidentification.